Evaluation of water safety plan implementation at provincial water utilities in Vietnam. (30th December 2022) - Nguyen, Viet-Anh; Tran Thi Hien, Hoa; Nijhawan, Anisha; Howard, Guy; Nghia Ton, Tuan
Abstract: This study evaluated the experience of implementing water safety plans (WSPs) in Vietnam. WSPs were introduced in Vietnam by the World Health Organization (WHO) in collaboration with the Ministry of Construction in 2006 and have been a mandatory requirement for municipal water supplies since 2012. Using a mixed-methods approach, we collected data on the perceived benefits and challenges of WSP implementation from 23 provincial water companies between August and November 2021. Potential public health benefits of improved water quality were a key motivation; 87% of the water utilities were also motivated by the risk of climate change and prepared response plans to climate-related extreme events as part of WSPs. A decrease in E. coli and an improvement in disinfectant residual in treated water were reported by 61 and 83% of the water supplies, respectively. Sixty-five percent of the water supplies also reported improved revenue and cost recovery. Key barriers to WSP implementation were a lack of WSP guidance suitable for the local context (87%) and insufficient funds for WSP implementation (43%). Our study highlights the need for improved support and capacity building along with locally suited guidance on WSP implementation and audit. HIGHLIGHTS: Increasing water pollution, emerging climate change, process of equitization, and expansion of service areas are important impacts on water safety plan (WSP). WSP has led to tangible benefits. The WSP is a useful vehicle for climate change adaptations, improve resilience. The commitment from Government and from water utilities is strong. The critical financial barriers, training needs, and support in WSP need to be addressed. Graphical Abstract